Hallazgos radiológicas en la isquemia mesentérica - Teresa Salero; Sérgio Pina (Sociedade Galega de Medicina Interna, 2021)
A 78-year-old man suffering from type 2 diabetes, hypertension, and severe obesity, presented to the Emergency Department with acute and generalized abdominal pain and distension, nausea and vomiting over 12 hours